Comparative cytotoxic and antiproliferative profile of methotrexate and fluorouracil on different ocular cells. Issue 7 (30th December 2020) - Schulz, André; Rickmann, Annekatrin; Julich‐Haertel, Henrike; Germann, Anja; von Briesen, Hagen; Januschowski, Kai; Szurman, Peter
Abstract: Purpose: To analyse the cytotoxic and antiproliferative effect of methotrexate (MTX) and fluorouracil (5‐FU) in vitro on fibroblasts, retinal pigment epithelial (RPE) and photoreceptor cells as an adjunct for reducing the incidence of proliferative vitreoretinopathy (PVR) after rhegmatogenous retinal detachment surgery. Methods: Methotrexate and 5‐FU were dissolved separately in balanced salt solution (BSS) with concentrations ranging from 0–8000 µg/ml and 0–4000 µg/ml, respectively. All solutions were analysed in terms of pH and osmolarity and applied for 1 h to fibroblasts (BJ), RPE (ARPE‐19) and photoreceptor (661W) cell lines adherently cultivated in 96‐well cell culture plates (10 000 cells/well). 24 h after incubation, the proliferative (BrdU), metabolic (CellTiter‐Glo) and apoptotic (Caspase 3/7) activity of the cells were examined in vitro. Results: 5‐FU had an antiproliferative effect on BJ and ARPE‐19 cells starting from low concentrations (2 µg/ml). However, the viability of 661W cells decreased and apoptosis was induced with increasing 5‐FU concentration. In contrast, MTX up to a concentration of 266 µg/ml did neither result in a significant loss of viability nor in increased caspase 3/7 activity of BJ, ARPE‐19 and 661W cells and inhibited the proliferation of ARPE‐19 already at low concentrations starting from 8 µg/ml. Conclusions: Methotrexate dissolved in BSS is biocompatible up to a concentration of 266 µg/ml and may act as an intraoperative rinse solution to inhibit RPE proliferation in PVR‐diseased eyes. Contrary, the use of 5‐FU within the posterior segment of the eye is limited by its cell‐damaging effect on photoreceptor cells.